Closing the Gap: Mouse Models to Study Adhesion in Secondary Palatogenesis. (October 2017) - Lough, K.J.; Byrd, K.M.; Spitzer, D.C.; Williams, S.E
Secondary palatogenesis occurs when the bilateral palatal shelves (PS), arising from maxillary prominences, fuse at the midline, forming the hard and soft palate. This embryonic phenomenon involves a complex array of morphogenetic events that require coordinated proliferation, apoptosis, migration, and adhesion in the PS epithelia and underlying mesenchyme. When the delicate process of craniofacial morphogenesis is disrupted, the result is orofacial clefting, including cleft lip and cleft palate (CL/P). Through human genetic and animal studies, there are now hundreds of known genetic alternations associated with orofacial clefts; so, it is not surprising that CL/P is among the most common of all birth defects. In recent years, in vitro cell-based assays, ex vivo palate cultures, and genetically engineered animal models have advanced our understanding of the developmental and cell biological pathways that contribute to palate closure. This is particularly true for the areas of PS patterning and growth as well as medial epithelial seam dissolution during palatal fusion. Here, we focus on epithelial cell-cell adhesion, a critical but understudied process in secondary palatogenesis, and provide a review of the available tools and mouse models to better understand this phenomenon.